Klasifikasi Erosi Permukaan Pada Area Reklamasi Tambang Batubara Menggunakan Universal Soil Loss Equation (Usle) - Fridtriyanda, Asri (ReTII, 2023)
Reclamation is an activity aimed at repairing or arranging the use of land disturbed by mining business activities so that it can function and be efficient according to its intended purpose. It is hoped that in planned and sustainable reclamation activities, ex-mining land can be used or reused as agricultural land or other productive activities so that the negative impacts of mining activities can be reduced. By looking at the importance of this reclamation activity, it is necessary to evaluate the level of success of reclamation which aims to evaluate the implementation of land use, control of erosion and sedimentation, implementation of revegetation and final settlement. Erosion is one of the factors that must be evaluated. This is because erosion control can result in environmental pollution outside the mining area because runoff water from the mining area flows into the river around the mining area, therefore it is necessary to classify erosion to determine the level of erosion that occurs in the Block 1 reclamation-revegetation area. Based on the data provided has been obtained, the annual soil erosion value at the Block 1 Reclamation location is 70.48 tons/Ha/year, which is in the medium category. Based on observations in the field, things that influence erosion in the Block 1 reclamation area are because erosion and sedimentation control structures were not built, plant growth was not optimal, and cover crops growth was not optimal in certain areas.